Viscosity and thermal conductivity comparative study for hybrid nanofluid in binary base fluids - Kumar V.; Sahoo R.R. (My University, 2025)
Thermal conductivity and viscosity analysis of Al2O 3/CuO (50/50) hybrid nanofluid in various mass fractions of ethylene glycol (EG) and propylene glycol (PG) binary base fluid have been investigated in the present work. Hybrid nanofluid with vol. fraction range limited to 1.5% and within the higher temperature range of 50°C to 70°C is considered for thermal conductivity and viscosity analysis. Impact on viscosity and conductivity models with various shape nanoparticles, i.e, spherical, cylindrical, brick, platelets, and blades have been discussed and were compared in EG and PG binary base fluids. Also, the analysis extends to the prediction for the stability with zeta potential and synthesis of spherical shape Al2O3/CuO hybrid nanofluid with X-ray diffraction (XRD) and scanning electron microscope (SEM). The theoretical analysis revealed that thermal conductivity of Al2O3/CuO hybrid nanofluid in EG binary base fluid is lower compared to in PG binary base fluid. The thermal conductivity is observed to be higher in spherical and cylindrical shape nanoparticle compared to bricks, blades, and platelets shape nanoparticles. Optimum viscosity of Al2O3/CuO hybrid nanofluid is observed at 50%EG and 30%PG of the binary base fluid. Hybrid nanofluid in 30% of PG as binary base fluid results 16.2% higher dynamic viscosity compared to pure PG base fluid for a volume concentration of 2%. Zeta potential measurement results in the stability of spherical Al2O3-CuO/ (50/50) EG/W hybrid nanofluid, and it may be considered as a heat transfer fluid. © 2019 Wiley Periodicals, Inc.